The ubiquitin-proteasome system and autophagy: Coordinated and independent activities. (October 2016) - Cohen-Kaplan, Victoria; Livneh, Ido; Avni, Noa; Cohen-Rosenzweig, Chen; Ciechanover, Aaron
Abstract: The living cell is an ever changing, responsive, and adaptive environment where proteins play key roles in all processes and functions. While the scientific community focused for a long time on the decoding of the information required for protein synthesis, little attention was paid to the mechanisms by which proteins are removed from the cell. We now realize that the timely and proper activity of proteins is regulated to a large extent by their degradation; that cellular coping with different physiological cues and stress conditions depends on different catabolic pathways; and that many pathological states result from improper protein breakdown. There are two major protein degradation systems in all eukaryotic cells—the ubiquitin- proteasome and the autophagy-lysosome. The two systems are highly regulated, and—via degradation of a broad array of proteins—are responsible for maintenance of protein homeostasis and adaptation to environmental changes. Each is comprised of numerous components responsible for its coordinated function, and together they encompass a considerable fraction of the entire genome. In this review, we shall discuss the common and diverse characteristics of the ubiquitin-proteasome system (UPS) and autophagy—their substructure, mechanisms of action, function and concerted regulation under varying pathophysiological conditions.